Prokaryotic ancestry and gene fusion of a dual localized peroxiredoxin in malaria parasites - Djuika, Carine F.; Huerta-Cepas, Jaime; Przyborski, Jude M.; Deil, Sophia; Sanchez, Cecilia P.; Doerks, Tobias; Bork, Peer; Lanzer, Michael; Deponte, Marcel (Microbial cell, 2015)
Prokaryotic ancestry and gene fusion of a dual localized peroxiredoxin in malaria parasites - Horizontal gene transfer has emerged as a crucial driving force for the evolution of eukaryotes. This also includes Plasmodium falciparum and related economically and clinically relevant apicomplexan parasites, whose rather small genomes have been shaped not only by natural selection in different host populations but also by horizontal gene transfer following endosymbiosis. However, there is rather little reliable data on horizontal gene transfer between animal hosts or bacteria and apicomplexan parasites. Here we show that apicomplexan homologues of peroxiredoxin 5 (Prx5) have a prokaryotic ancestry and therefore represent a special subclass of Prx5 isoforms in eukaryotes. Using two different immunobiochemical approaches, we found that...